Little Leaguer`s Shoulder - Frick, E.; Hilgers, M. P. (International Journal of Athletic Therapy & Training, 2015)
A 14-year-old right-handed male baseball pitcher comes to you complaining of right shoulder pain for several weeks. He recalls no injury to his shoulder but instead complains of slowly worsening pain with throwing. Between travel and now high school baseball, which just recently resumed, he often finds himself pitching in multiple games per week. As you examine the athlete, you discover tenderness to palpation over the lateral aspect of his right shoulder...